Vacuum-assisted stereotactic breast biopsy in the diagnosis and management of suspicious microcalcifications - Gül Esen; Burçin Tutar; Cihan Uras; Zerrin Calay; Ümit İnce; Onur Tutar (Diagnostic and Interventional Radiology, 2016)

(untitled)
PURPOSE:We aimed to present our biopsy method and retrospectively evaluate the results, upgrade rate, and follow-up findings of stereotactic vacuum-assisted breast biopsy (VABB) procedures performed in our clinic.METHODS:Two hundred thirty-four patients with mammographically detected nonpalpable breast lesions underwent VABB using a 9 gauge biopsy probe and prone biopsy table. A total of 195 patients (median age 53 years, range 32–80 years) with 198 microcalcification-only lesions with a follow-up of at least one year were included in the study. The location of the lesion relative to the needle was determined from the postfire images, and unlike the conventional technique, tissue retrieval was predominantly performed from that location, followed by a complete 360° rotation, if needed.RESULTS:The median core number was 8.5. Biopsy results revealed 135 benign, 24 atypical, and 39 malignant lesions. The total upgrade rate at surgery was 7.7% (6.1% for ductal carcinomas in situ and 10.5% for atypical lesions). Patients with benign lesions were followed up for a median period of 27.5 months, with no interval change. At the follow-up, scar formation was seen in 23 patients (17%); three of the scars were remarkable for resembling a malignancy.CONCLUSION:Our biposy method is fast and practical, and it is easily tolerated by patients without compromising accuracy. Patients with a diagnosis of atypia still need to undergo a diagnostic surgical procedure and those with a malignancy need to undergo curative surgery, even if the lesion is totally excised at biopsy. VABB may leave a scar in the breast tissue, which may resemble a malignancy, albeit rarely.